PERILAKU KEWIRAUSAHAAN DAN PEMASARAN DALAM MENINGKATKAN PENDAPATAN STUDI PADA USAHA ORIANA MINI MART - Gede Yudi Pratama (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
Entrepreneurship is a way of thinking, studying, and acting that is based on business opportunities, a holistic approach, and leadership. With entrepreneurship, the government hopes that all elements of society can create equal employment opportunities so that it can reduce the unemployment rate in Indonesia. Oriana Mini Mart is a business store engaged in the retail business that sells some basic needs for the local community. This business certainly relies on the expertise of employees or labor both in terms of waiters. This type of research is a qualitative research that seeks to collect facts and circumstances properly through interviews. The interview technique used is a structured interview which guides the interviewees to ask various questions to the informants. Interviews were conducted with business owners, employees/ti, and several consumers. The results showed that entrepreneurial behavior through innovation, decision making in dealing with business risks, and taking existing opportunities, was very effective in increasing income at Oriana Mini Mart. In addition, the marketing carried out by Oriana Mini Mart also plays an effective role in increasing revenue through price and product management, as well as promotions carried out. And supported by a quite strategic location